2010
DOI: 10.1186/1471-2121-11-29
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells rescue cardiomyoblasts from cell death in an in vitro ischemia model via direct cell-to-cell connections

Abstract: Background: Bone marrow derived mesenchymal stem cells (MSCs) are promising candidates for cell based therapies in myocardial infarction. However, the exact underlying cellular mechanisms are still not fully understood. Our aim was to explore the possible role of direct cell-to-cell interaction between ischemic H9c2 cardiomyoblasts and normal MSCs. Using an in vitro ischemia model of 150 minutes of oxygen glucose deprivation we investigated cell viability and cell interactions with confocal microscopy and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 37 publications
(45 reference statements)
5
124
0
1
Order By: Relevance
“…Cell-to-cell contacts may also imply the formation of a network of nanotubes between neighboring cells, as described for cardiomyoblasts and MSCs in vitro (Cselenyak et al, 2010).…”
Section: The Involvement Of Cellular Junctional Coupling Where Membramentioning
confidence: 92%
“…Cell-to-cell contacts may also imply the formation of a network of nanotubes between neighboring cells, as described for cardiomyoblasts and MSCs in vitro (Cselenyak et al, 2010).…”
Section: The Involvement Of Cellular Junctional Coupling Where Membramentioning
confidence: 92%
“…When therapeutically injected, human MSCs have also shown to promote arteriogenesis of ischemic myocardium (11) and the results of most clinical studies are promising (12). A mechanistic explanation for these results might be capacity of MSCs to rescue cardiomyoblasts from cell death, which has recently been demonstrated in an in vitro ischemia model (13).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that added mesenchymal stem cells could improve the survival of postischemic cardiac cells. Confocal microscopy images revealed direct cell-to-cell interactions, such as partial membrane connection or intercellular nanotubes, which probably play an important role in the observed protection 10 . These nanotubes span over distances of several cell diameters, and their diameters were between 200 and 500 nm (white arrows).…”
Section: Representative Resultsmentioning
confidence: 96%
“…In case of co-cultures, MSCs can be distinguished from H9c2 cells due to their Vybrant DiD cell labeling. The ratio of dead cells can be evaluated in 4 independent fields of view (objective 10x) for each culture in a blind fashion 10 .…”
Section: Analysis With Confocal Microscopymentioning
confidence: 99%